Consumer’s Purchase Intention on Sustainable and Greener Liquid Laundry Pods Driven by Green Innovation and Green Brand - Naryanton Naryanton; Zoel Hutabarat (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
This study examines the factors influencing consumer purchase intention toward environmentally friendly laundry pods in Indonesia, a country facing severe waste challenges and increasing demand for sustainable products. The research aims to analyze how green product innovation, green perceived quality, green customer value, and attitude toward green brand shape purchase intention in the context of eco friendly household products. Using a quantitative correlational design, data were collected through an online questionnaire from 135 respondents who use washing machines and have experience with laundry pods. The data were analyzed using Partial Least Squares Structural Equation Modeling through SmartPLS 4. The results show that green product innovation positively affects green customer value and purchase intention, while green customer value significantly influences both purchase intention and attitude toward green brand. Green perceived quality also has a direct positive effect on purchase intention. However, attitude toward green brand does not significantly predict purchase intention, and its mediating role is not supported. In contrast, green customer value successfully mediates the relationship between green product innovation and purchase intention. These findings highlight the importance of product innovation and perceived value in strengthening consumer interest in sustainable household products.